2002
DOI: 10.1002/qj.200212858315
|View full text |Cite
|
Sign up to set email alerts
|

A study on the optimization of the deployment of targeted observations using adjoint‐based methods

Abstract: SUMMARYA new adjoint-based method to find the optimal deployment of targeted observations, called Kalman Filter Sensitivity (KFS), is introduced. The major advantage of this adjoint-based method is that it allows direct computation of the reduction of the forecast-score error variance that would result from future deployment of targeted observations. This method is applied in a very simple one-dimensional context, and is then compared to other adjoint-based products, such as classical gradients and gradients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…In data assimilation problems [1][2][3][6][7][8][9][10][11][12][13][14], usually, the cost functional (discrepancy between observations and model calculations) is minimized and assumes the following form:…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…In data assimilation problems [1][2][3][6][7][8][9][10][11][12][13][14], usually, the cost functional (discrepancy between observations and model calculations) is minimized and assumes the following form:…”
Section: Problem Statementmentioning
confidence: 99%
“…In [13,14] the optimization of observations was conducted via direct computation of a reduction of the error variance of forecast score caused by additional observations. The variance of forecast score was expressed through adjoint sensitivity gradients and the covariance matrix of analysis (initial state) error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of uncertainty is expressed with respect to the forecast without any added observations. Several (so-called targeting) techniques for computing deployments have been developed at national meteorological services: the Ensemble Transform Kalman Filter (ETKF, Bishop et al, 2001); singular vectors (Palmer et al, 1998); the Kalman Filter Sensitivity (KFS, Bergot and Doerenbecher, 2002). The last technique has been developed at Météo-France and implemented in the numerical model ARPÈGE in research mode.…”
Section: Introductionmentioning
confidence: 99%
“…This is called the targeted observations technique. Different techniques for the placement of obser-vations in the context of numerical weather prediction models are discussed in [9,78,66,49,77,72,7]. Studies performed during field experiments revealed the potential benefits that may be achieved using adaptive observations as well as various practical issues and shortcomings of the current targeting methodologies.…”
Section: Optimal Placement Of Observationsmentioning
confidence: 99%